2016
DOI: 10.1038/srep26162
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of indium-tin-oxide nanoparticles by macrophages provokes pyroptosis requiring NLRP3-ASC-Caspase1 axis that can be prevented by mesenchymal stem cells

Abstract: The biological effects of indium-tin-oxide (ITO) are of considerable importance because workers exposed to indium compounds have been diagnosed with interstitial lung disease or pulmonary alveolar proteinosis; however, the pathophysiology of these diseases is undefined. Here, mice intraperitoneally inoculated with ITO-nanoparticles (ITO-NPs) resulted in peritonitis dependent in NLRP3 inflammasome, with neutrophils recruitment and interleukin-1β (IL-1β) production. Withal peritoneal macrophages exposed ex vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 64 publications
2
44
0
Order By: Relevance
“…THP‐1 Knockdown Cell Lines : Four different THP‐1 monocytic cell lines (Null‐1, defASC, defNLRP3, and defCaspase‐1) were obtained from InvivoGen (France). The THP‐1 null and knockdown cells were cultured according to the manufacturers' instructions. After sub‐culturing the cells thrice in RPMI‐1640 cell medium supplemented with 10% FBS, cells were seeded in 96‐well plates at a density of 10 5 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…THP‐1 Knockdown Cell Lines : Four different THP‐1 monocytic cell lines (Null‐1, defASC, defNLRP3, and defCaspase‐1) were obtained from InvivoGen (France). The THP‐1 null and knockdown cells were cultured according to the manufacturers' instructions. After sub‐culturing the cells thrice in RPMI‐1640 cell medium supplemented with 10% FBS, cells were seeded in 96‐well plates at a density of 10 5 cells per well.…”
Section: Methodsmentioning
confidence: 99%
“…This cell death was RIPK1-independent but caspase1-dependent, and thus identified as pyroptosis. The authors speculated that the pyroptosis induced by ITO-NPs in macrophages may be a mechanism of exacerbated inflammation in the lungs after inhalation (Naji et al, 2016).…”
Section: Mechanistic Studies In Vivo/ex Vivo/in Vitro On Inflammationmentioning
confidence: 99%
“…Emerging studies suggest that MSCs can inhibit RCD such as necroptosis [], and we recently showed that MSCs could prevent pyroptosis in macrophages []. We focused on the pathogenesis of severe occupational lung diseases such as interstitial lung disease and pulmonary alveolar proteinosis, which could involve pyroptosis of lung macrophages caused by inhalation of inorganic particles []. This pyroptosis is characterized by the production of inflammatory cytokines and cell death by cytolysis, events depending on the inflammasome NACHT, LRR, and PYD domain‐containing protein 3–apoptosis‐associated speck‐like protein containing a CARD–Caspase‐1 (NLRP3‐ASC‐Caspase‐1) [].…”
Section: Msc Function To Modulate Rcd As Criteria For Therapeutic Usementioning
confidence: 99%
“…Features of RCD and ACD with the role of MSCs in preventing RCD in terminally differentiated third-party cells Data are based mostly on the studies reported in[22,23,33,34,[43][44][45][46]. Additional citations can be found throughout the article.The plasma membrane of cells undergoing apoptosis remains intact but not with efferocytosis failure, during which cells might progress to secondary necrosis.…”
mentioning
confidence: 99%